Track of CARTHE surface drifter M158_76-1 - Hans, Anna Christina; Brandt, Peter (GEOMAR - Helmholtz Centre for Ocean Research Kiel, 2021)
The CARTHE drifters are microstar drifting buoys that track currents at 1 meter beneath the surface. The data are acquired by Pacific Gyre.